(3GdETGQGJ Edi HjGf GdCSeGA GdeHgeGJs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdNWjH GdHZOGOj , CHh HcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOj,J (B463 (3g` s ((3SHW Hf GdYLei EHQGgje Hf eMeO Hf Ndjd s)
(3ChdgG (B:s
(3GdMeO ddg HGQF GdeUfhYGJ heOHQ GdeMOKGJ CeG HYO aEf Yde GdMOjK (B[ (3ef CfaS GdTQjYI hChdi eG JQZH ajg GUMGH GdGfaS GdRcjI s
(3BNQgG (B:s
(3bGd eUfag GdTjN GdEeGe GdYdGeI eMi GdOjf CHh RcQjG (B: (3aQZJ efg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B68 - (3U(B98s
(3GdfSNI HgG MhGTs
(3hgh GdCSeGA GdeHgeI ai GdCMGOjKs
(3hgh eNJUQ dcJGH GdNWjH GdHZOGOj ai gPG GdehVhYs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs